Tafsir ChatGPT : (Tinjauan Terhadap Kemampuan & Batasan dalam Komunikasi AI Terhadap Penafsiran Al-Qur’an) - Muawal, Hamid Nazar; Ursa Agniya (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2024)
The growth of artificial intelligence (AI) technology has brought significant progress in various aspects of human life, including in the field of religion. One application that is attracting attention is AI's ability to provide interpretations of sacred texts, including the Al-Qur'an. This research aims to explore the capabilities and limitations of ChatGPT, a language-based AI model, in providing interpretation of the Al-Qur'an. This study uses a qualitative approach with content analysis to evaluate the quality of interpretations produced by ChatGPT regarding Al-Qur'an verses. The research results show that although ChatGPT is able to provide quite good interpretations of several verses of the Al-Qur'an, there are several limitations that need to be considered. ChatGPT tends to produce better interpretations of verses that have clear and limited context. More complex or ambiguous verses tend to be difficult for ChatGPT to understand, which can result in inaccurate or erroneous interpretations. ChatGPT has limitations in understanding the cultural, historical and linguistic context contained in the Al-Qur'an. This research concludes that although ChatGPT shows potential in providing interpretations of the Al-Qur'an, further development is still needed to improve the quality and depth of the interpretations produced. Therefore, the results of ChatGPT interpretation need to be considered carefully and always accompanied by a deep human understanding of the text of the Qur’an.